Reduced abundance of Faecalibacterium prausnitzii in the gut microbiota of children diagnosed with cancer, a pilot study - de Muinck, Eric J.; Trosvik, Pål; Nguyen, Nga; Fashing, Peter J.; Stigum, Vetle M.; Robinson, Nina; Hermansen, Johanne U.; Munthe-Kaas, Monica C.; Baumbusch, Lars O. (Frontiers in Microbiomes, 2023)
Background: There is an increasing awareness of the importance of the gut microbiome in disease progression and the maintenance of human health. However, links between the microbiome and cancer onset remain relatively unexplored. This is especially the case for childhood cancers, which although rare, are the predominant cause of death among children in Western countries.Methods: Fecal samples were collected from patients, before the onset of treatment, by the Norwegian Childhood Cancer Biobank in Oslo and from children attending kindergartens in Oslo, Norway. Using 16S rRNA gene amplicon sequencing, we compared the gut microbiome compositions of the children diagnosed with cancer with children attending kindergarten.We observed significant differences in the relative abundances of several taxa, including a striking depletion of Faecalibacterium prausnitzii, an important taxa linked to gut health maintenance.Our observations provide evidence that the gut microbiome may play an important role in physiological changes associated with the onset of childhood cancer. However, further studies should be designed in order to validate our findings. Furthermore, these results suggest that variations in the microbial community could potentially be used as an early indicator of childhood cancer.